Chitosan and oligo(DL-lactic acid) networks: Correlations between physical properties and macromolecular configuration - Ciulik, Claudio B.; Bernardinelli, Oigres D. [UNESP]; Azevedo, Eduardo R. de [UNESP]; Akcelrud, Leni (Elsevier B.V., 2016)
Aiming the obtainment of materials with useful properties for bio-applications, as thermal and mechanical (in particular flexibility), chitosan and low molecular weight poly(lactic acid) were chosen due to their biodegradability and biocompatibility in various bio-environments. Networks formed by oligo( DL-lactic acid) segments linked to the chitosan chains were prepared, in which the ratio between the components varied systematically. A thorough structural characterization was performed, including the degree of crosslinking and the size of the crosslinking blocks. The thermal and mechanical properties varied according the ratio between the components in a non-linear way, which was discussed in terms of the macromolecular architecture. The data were compared with previous results obtained for grafts with the same composition aiming to verify the effect of the macromolecular architecture on the macroscopic properties. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Oligo(DL-Lactic acid); Networks